Radical attitude: interview with costume designer Verônica Julian (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
In this interview, carried out as part of the master's research that I have been developing in the postgraduate program in Performing Arts at the Federal University of Goiás, on teaching costume design in Brazil, I invite costume designer Verônica Julian to share some of her almost 30 years in the profession and think about teaching costume design from the perspective of informal education. I have come to understand this teaching modality based on the construction of autonomous learning paths for the stages of making costumes, as well as the daily learning of work in workshops and collections. As a result of the interview, the experiences and memories reported by Verô, as we usually call her, stood out and brought layers as important as the answers I wanted and assumed to obtain. A woman with a “radical attitude”.
Keywords: costume design; informal teaching; studio; theater; audio-visual